Exosomal circPOLQ promotes macrophage M2 polarization via activating IL-10/STAT3 axis in a colorectal cancer model - Yang Liu; Chen Chen; Jinbo Liu; Zhenqiang Sun; Bo Shao; Yanxin Xu; Pengyuan Dang; Shengyun Hu; Haifeng Sun; Chaoguan Wang; Junhong Hu (Journal for ImmunoTherapy of Cancer)
Background Accumulating evidence demonstrates that an increased tumor-associated macrophage abundance is often associated with poor prognosis in colorectal cancer (CRC). The mechanism underlying the effect of tumor-derived exosomes on M2 macrophage polarization remains elusive.Results The novel circular RNA circPOLQ exhibited significantly higher expression in CRC tissues than in paired normal tissues. Higher circPOLQ expression was associated with poorer prognosis in patients with CRC. In vitro and in vivo experiments showed that tumor-derived exosomal circPOLQ did not directly regulate CRC cell development but promoted CRC metastatic nodule formation by enhancing M2 macrophage polarization. circPOLQ activated the interleukin-10/signal transducer and activator of transcription 3 axis by targeting miR-379–3 p to promote M2 macrophage polarization.Conclusion circPOLQ can enter macrophages via CRC cell-derived exosomes and promote CRC metastatic nodule formation by enhancing M2 macrophage polarization. These findings reveal a tumor-derived exosome-mediated tumor–macrophage interaction potentially affecting CRC metastatic nodule formation.